Research on the suitability improvement of the standard of green campus in China based on STARS - B.F. Zhu; Y. Zhou; J. Ge (International Association of Lowland Technology, 2016)
Under the tide of green building, many countries introduce actively evaluation standards of green campus and develop the construction of green campus. China introduced the Green Campus Evaluation Standards (CSUS / GBC04-2013) (short for Standard in the following) subsequently. While compared with green campus evaluation standards of other countries, it is still in the start stage and has many shortcomings, for this reason, in order to optimize Standard by studying United States green campus evaluation standard STARS. Comparing China’s standard with the US STARS2.0 to analyze the differences and the cause of differences from the three aspects including the organization model, methods and contents of evaluation. Then combined with China's actual situation to analyze the suitability of application of STARS in our country. Finally, study the reasonable place of the STARS, from three aspects to provide Standard with concrete improvement suggestions and give China’s green campus construction a better guidance.